Rancangan Aplikasi Inventory Barang Pada Babycom Berbasis Web Menggunakan Metode Waterfall - Akbar Ikhsan Pratama (Saturnus: Jurnal Teknologi dan Sistem Informasi, 2024)
Babycom, a company specializing in the sale of imported baby sandals, faces challenges in managing its inventory due to rapid sales growth, particularly through the Tiktok Shop platform. Manual inventory management is prone to data inaccuracies, monitoring difficulties, and inefficient resource utilization. To address these issues, this research proposes the development of a web-based inventory management application using the waterfall development method. This approach is chosen for its ability to provide structured guidance from needs analysis to maintenance, tailored to the complexity of Babycom's requirements. It is anticipated that this design will offer an effective solution to inventory management issues, resulting in improved operational efficiency, data accuracy, and ease of information access for the company.